The Search for Double Beta Decay With Germanium Detectors: Past, Present, and Future - Avignone III, Frank T.; Elliott, Steven R. (Frontiers in Physics, 2019)
High Purity Germanium Detectors have excellent energy resolution; the best among the technologies used in double beta decay. Since neutrino-less double beta decay hinges on the search for a rare peak upon a background continuum, this strength has enabled the technology to consistently provide leading results. The Ge crystals at the heart of these experiments are very pure; they have no measurable U or Th contamination. The added efforts to reduce the background associated with electronics, cryogenic cooling, and shielding have been very successful, leading to the longevity of productivity. The first experiment published in 1967 by the Milan group of Fiorini, established the benchmark half-life limit >3×10^20 yr. This bound was improved with the early work of the USC-PNNL, UCSB and Milan groups yielding limits above 10^23 yr. The Heidelberg-Moscow and USC-PNNL collaborations pioneered the use of enriched Ge for detector fabrication. Both groups also initiated techniques of analyzing pulse waveforms to reject γ-ray background. These steps extended the limits to just over 10^25 yr. In 2000, a subset of the Heidelberg-Moscow collaboration claimed the observation of double beta decay. More recently, the and GERDA collaborations have developed new detector technologies that optimize the pulse waveform analysis. As a result, the GERDA collaboration refuted the claim of observation with a revolutionary approach to shielding by immersing the detectors directly in radio-pure liquid argon. In 2018, the collaboration, using a classic vacuum cryostat and high-Z shielding, achieved a background level near that of GERDA by developing very pure materials for use nearby the detectors. Together, GERDA and have provided limits approaching 10^26 yr. In this article, we elaborate on the historical use of Ge detectors for double beta decay addressing the strengths and weaknesses. We also summarize the status and future as many and GERDA collaborators have joined with scientists from other efforts to give birth to the LEGEND collaboration. LEGEND will exploit the best features of both experiments to extend the half-life limit beyond 10^28 yr with a ton-scale experiment.